Chinese and Western Musical Training Impacts the Circuit in Auditory and Reward Systems - Guo, Sijia; Peng, Ke; Ding, Rui; Zhou, Junchen; Liu, Yan; He, Yao; Liu, Yuhong; Li, Ke; Liu, Pei; Luo, Cheng; Lu, Jing; Yao, Dezhong (Frontiers in Neuroscience, 2021)
Previous studies have provided evidence about the brain plasticity effects of musical training, however, the issue of how expertise in music styles induced by Chinese or Western musical training affects neuroplasticity and reward responses has been less considered, especially for subjects of Chinese origin. In this work, 16 musicians who trained in the Western music style (Western-trained musicians) and 18 musicians who trained in the Chinese music style (Chinese-trained musicians) were recruited as the musician group for the experiment, while 15 nonmusicians were recruited as the control group. Using a paradigm that consisted of listening to Chinese and Western music and measurements using functional magnetic resonance imaging (fMRI) technology, we found that Chinese-trained musicians activated the bilateral superior temporal gyrus (STG) when listening to music, while Western-trained musicians activated the left STG. In addition, under the condition of listening to music with Chinese style, Chinese-trained musicians have a stronger functional connection in the circuit of the auditory and reward system than Western-trained musicians. The finding is opposite under the condition of listening to music with Western style. Interestingly, it seems that the circuit of Chinese-trained musicians is partial to the right STG, while Western-trained musicians show the opposite, i.e., a tendency towards the left STG. The influence of different music styles on experienced musicians is reflected by the functional activities and connections between the auditory system and the reward system. This outcome indicates that training in Chinese music style or Western music style affects the strategies of musicians when listening to music. Musical characteristics such as rhythm, melody and cultural attributes play an important role in this process. These findings, which provide evidence for functional neuroplasticity based on musical training, can enrich our insights into the musical brain.